Comparing different methods of human breast milk fortification using measured v. assumed macronutrient composition to target reference growth: a randomised controlled trial. Issue 3 (2nd December 2015) - McLeod, Gemma; Sherriff, Jill; Hartmann, Peter E.; Nathan, Elizabeth; Geddes, Donna; Simmer, Karen
Abstract: The variable content of human breast milk suggests that its routine fortification may result in sub-optimal nutritional intakes and growth. In a pragmatic trial, we randomised infants born below 30 weeks of gestation to either the intervention (Igp) of fortifying milk on measured composition according to birth weight criteria and postmenstrual age (PMA) or our routine practice (RPgp) of fortifying on assumed milk composition to target 3·8–4·4 g protein/kg per d and 545–629 kJ/kg per d. Milk composition was measured using the MIRIS® Human Milk Analyser. Percentage fat mass (%FM) was measured using PEA POD (COSMED). The effects of macronutrient intakes and clinical variables on growth were assessed using mixed model analysis. Mean measured protein content (1·6 g/100 ml) was higher than the assumed value (1·4 g/100 ml), often leading to lower amounts of fortifier added to the milk of intervention infants. At discharge (Igp v. RPgp), total protein (3·2 (sd 0·3) v . 3·4 (sd 0·4) g; P =0·067) and energy (456 (sd 39) v. 481 (sd 48) kJ; P =0·079) intakes from all nutrition sources, weight gain velocity (11·4 (sd 1·4) v. 12·1 (sd 1·6) g/kg per d; P =0·135) and %FM (13·7 (sd 3·6) v. 13·6 (sd 3·5) %; P =0·984) did not significantly differ between groups. A protein intake >3·4 g/kg per d reduced %FM by 2 %. Nutrition and growth was not improved by targeting milk fortification according to birth weight criteria and PMA using measured milk composition, compared with routine practice. Targeting fortification on measured composition is labour intensive, requiring frequent milk sampling and precision measuring equipment, perhaps reasons for its limited practice. Guidance around safe upper levels of milk fortification is needed.